Spherical Modes Driven Directional Modulation with a Compact MIMO Antenna - Zandamela, Abel Abdul; Marchetti, Nicola; Narbudowicz, Adam (My University, 2023)
In this letter, a compact beamsteering MIMO antenna is proposed for Directional Modulation (DM) applications. A generalization of the beamsteering principle is presented and by exploiting the antenna’s unidirectional beamsteering capability within the entire azimuth plane, the system realizes secure steerable transmissions in the direction of the legitimate receiver, with a low Bit Error Rate (BER) of 10^(-5), while a high error rate of 10^(-1) is seen outside the desired regions. Numerical and experimental verifications are carried out to validate the proposed concept and comparisons with circular arrays are conducted, revealing that the system achieves comparable performance but with up to 35% and 71% reduction in antenna diameter and profile, respectively. The method is proposed as a good candidate to enhance the security of small (IoT) devices.
PUBLISHED
Keywords: Internet of Things; Small IoT Devices; Beamforming Antennas; Physical Layer Security; Directional Modulation; MIMO Antennas; Telecommunications; Beamforming; Directional Modulation; Internet of Things; Physical Layer Security; SMALL ANTENNAS; Spherical Modes Analysis